Sleep disordered breathing in motor neurone disease - D’Cruz, Rebecca F.; Murphy, Patrick B.; Kaltsakas, Georgios (Journal of Thoracic Disease; Vol 10, Supplement 1 (January 24, 2018): Journal of Thoracic Disease (Dedicated to the 3rd Clinical Update Sleep: International Conference 2018, Endorsed by ERS), 2018)
Motor neurone disease (MND) is a neurodegenerative disease defined by axonal loss and gliosis of upper and lower motor neurones in the motor cortex, lower brainstem nuclei and ventral horn of the spinal cord. MND is currently incurable and has a poor prognosis, with death typically occurring 3 to 5 years after disease onset. The disease is characterised by rapidly progressive weakness leading to paralysis, fasciculations, bulbar symptoms (including dysarthria and dysphagia) and respiratory compromise. Respiratory complications arise as a result of weakness of upper airway (pharyngeal and laryngeal) muscles and respiratory muscles (diaphragm, intercostal and accessory muscles) leading to respiratory failure. Due to early involvement of respiratory muscles in MND, sleep disordered breathing (SDB) occurs at a higher frequency than compared to the general population. SDB usually precedes daytime respiratory symptoms and chronic respiratory failure. It signi cantly impacts upon patients’ quality of life and survival and its presence may predict prognosis. Managing SDB in MND with non-invasive ventilation (NIV) improves quality of life and survival. Early identi cation and management of SDB in MND patients is therefore crucial. This update will review assessments of respiratory muscle function, types of SDB and the effects of NIV in patients with MND.